Biodiesel Preparation from Decanter Cake with Solid Acid Catalyst - Nurul Hajar , Embong; Gaanty Pragas, Maniam; Mohd Hasbi, Ab. Rahim (World Academy of Research and Publication, 2014)
Biodiesel is a renewable, biodegradable, non-toxic and has low emissions of CO, SO2, particulates and hydrocarbons fuel compared with the conventional diesel which can be easily produced through transesterification reaction. However, current commercial obstacle for biodiesel production is uneconomical and impractical due to high feedstock cost. Therefore in this study, decanter cake (DC), waste from oil palm mill was used as a feedstock for biodiesel production can be a better alternative. DC is a solid waste produced when the crude palm oil is centrifuged for purification where the supernatant is the purer palm oil and the sediment is called the decanter cake. Waste oil which has been classified as low-grade oil usually suffered with high free fatty acids (FFA) content. Catalyst selection has to be made wisely so that it can work for both esterification of free fatty acid which is present in DC-oil, and transesterification of triglycerides. In the present work, a solid acid catalyst comprising SO4 2−/TiO2–SiO2 was prepared, characterized and studied for its activity for the production of biodiesel. The silica source was obtained from biomass rice husk ash (RHA) which is available abundantly and low in cost as it also categorized as a waste. In addition, solid asid catalyst, SO42-/TiO2-SiO2 showed the potential in esterification reaction of decanter cake. About 91% of methyl ester yield was produced at 13 wt.% catalyst loading, 15:1 of methanol ratio to oil and 5 hours reaction at 120°C.